The Correlation between Controllers’ Aviation Knowledge, Listening Comprehension, and IELP at JATSC - Suryadi Suryadi (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2020)
The aim of this research is to find the correlation between controllers’ aviation knowledge mastery, listening comprehension and ICAO English Language Proficiency (IELP) at Jakarta Air Traffic Services Centre (JATSC). This research focused on controllers as the homogeneity respondent hence the random sampling was the suitable way to get the data. Respondents were selected without taking account of anything. The researcher used quantitative approach method to carry on the project because it was believed that the data would be numerical thing. Meanwhile variable instrument that researcher deployed namely a test. The test itself provided for respondents was implemented into three items. Having got the data after finalising the test, it was analysed by using Product Moment Correlation. The data then was calculated using that method and the result was r calculation 0.371535165 and it was higher than 0.349 and it meant that there was correlation between controllers’ aviation knowledge mastery, listening comprehension and IELP.